Green energy development in an industrial region: A case-study of Sverdlovsk region - Anzhelika Karaeva (Elsevier, 2021)
The development of renewable energy is one of the strategic directions of eco-modernization of the Russian energy sector, which will not only reduce the negative impact of the industry on the environment, but also provide remote territories with the stable access to electricity. Despite the fact that the Russian regions have a great potential for the development of renewable energy, the full transition of the energy sector to the ”green” vector of its development is currently impossible. Moreover, most of current studies consider the development of renewable energy without reference to the regions, which, according to the authors, does not provide an objective assessment of the potential for the use of renewable energy in Russia. The purpose of the present research is to evaluate the potential for the introduction of various renewable energy sources (RES) in the energy sector of the Sverdlovsk region — one of the largest industrial regions of Russia. The full-scale assessment of their potential use at the regional level helps to accelerate the process of their introduction into the energy sector, since during the assessment, scientists analyze not only the possibilities of use, but also the barriers to development. Authors applied various research methods among which analysis of state programs, analysis of the official statistical reports, analysis of natural conditions on the territory of the region, etc. As a result, authors developed a map of potential use of renewables in the territory of Sverdlovsk region, evaluated prospects of their development and revealed key barriers. The proposed algorithm of assessment might be applicable for other Russian regions.